Self-Healing Microcapsule-Thickened Oil Barrier Coatings - Alane Tarianna O. Lim; Chenlong Cui; Hee Dong Jang; Jiaxing Huang (Research, 2019)
Low-viscosity oils could potentially act as self-healing barrier coatings because they can readily flow and reconnect to heal minor damage. For the same reason, however, they typically do not form stable coatings on metal surfaces. Increasing viscosity helps to stabilize the oil coating, but it also slows down the healing process. Here, we report a strategy for creating highly stable oil coatings on metal surfaces without sacrificing their remarkable self-healing properties. Low-viscosity oil films can be immobilized on metal surfaces using lightweight microcapsules as thickeners, which form a dynamic network to prevent the creep of the coating. When the coating is scratched, oil around the opening can rapidly flow to cover the exposed area, reconnecting the particle network. Use of these coatings as anticorrosion barriers is demonstrated. The coatings can be easily applied on metal surfaces, including those with complex geometries, both in air or under water, and remain stable even in turbulent water. They can protect metal in corrosive environments for extended periods of time and can self-heal repeatedly when scratched at the same spot. Such a strategy may offer effective mitigation of the dangerous localized corrosion aggravated by minor imperfections or damage in protective coatings, which are typically hard to prevent or detect, but can drastically degrade metal properties.